Densities of electronic states for substitutionally disordered alloys - Yildiz, AK; Beeby, JL (Iop Publishing Ltd, 1999)
A formal treatment of the theory of the electronic density of stares for substitutional alloys is considered and the results of applications to a simple case are presented. The method is self-consistent, simple in computation and readily extended to ternary and more complex alloys. Numerical examples are given for the tight-binding limit.
Keywords: Space Recursive Technique; Random Binary-Alloys